Features of communicative competence and adaptation of Latin American students at different stages of learning - Z V Boyko; K G Marin Jerez (Peoples' Friendship University of Russia (RUDN University), 2011)
This article analyzes the results of the study of communicative competence and adaptation of students from Latin America. The article compares the features of adaptation and communicative competence of Hispanic students living in Russia for 1-2 and 4-5 years.